Islamic Economic Perspective on the Implementation of Michael F. Porter's Theory in Business Strategy Management - Amin, Muh Sirojuddin; Rachmadi, Kartika Rose (ITB AAS INDONESIA Surakarta, 2024)
This study uses a qualitative approach which aims to explain the competitive advantage strategy of the Sunan Drajat Islamic Boarding School business using. The qualitative method used is SWOT analysis. After the SWOT analysis, the researcher researched based on the theory of competitive advantage developed by Michael E. Porter which consists of Value Chain, Porte's Dynamic Diamond and Porter's Five Forces. The data collection used was observation, interview, documentation, observation and participation techniques. Then check the validity of the data using the triangulation method. From the research results, the Sunan Drajat Islamic Boarding School business in carrying out its activities it is based on the principles of benefit, honesty, justice, free from gharar and trust. Meanwhile, the results of the Porter's diamond model analysis found that the Sunan Drajat Islamic Boarding School business applies sharia principles, with the relationship between the main factors supporting each other. As for the results of Porter's Five Forces, it can be concluded that from the field data there are similarities between several components with the theory and there are some that are not in accordance with the theory. From the analysis that has been mentioned, it can be concluded that the PPSD Business uses an image differentiation strategy in marketing its products to remain superior in the midst of many similar business.